2014
DOI: 10.1068/p7616
|View full text |Cite
|
Sign up to set email alerts
|

Human Discrimination of Depth of Field in Stereoscopic and Nonstereoscopic Photographs

Abstract: Abstract. Depth of field (DOF) is defined as the distance range within which objects are perceived as sharp. Previous research has focused on blur discrimination in artificial stimuli and natural photographs. The discrimination of DOF, however, has received less attention. Since DOF introduces blur which is related to distance in depth, many levels of blur are simultaneously present. As a consequence, it is unclear whether discrimination thresholds for blur are appropriate for predicting discrimination thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The size of the stimuli displayed on the screens was constrained by the visual angle of the camera. More details could be seen in the authors' previous work [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the stimuli displayed on the screens was constrained by the visual angle of the camera. More details could be seen in the authors' previous work [14].…”
Section: Methodsmentioning
confidence: 99%
“…For each scene, six levels of depth of field were created via manipulating the aperture size of the camera: F2, F3.2, F5, F8, F13, and F20. These six levels of depth of field were definitely able to be discriminated by observers [14]. F2 represented the smallest depth of field and F20 represented the largest depth of field.…”
Section: Methodsmentioning
confidence: 99%
“…We labelled these photographs into eight categories according to their content: animals, architecture, flowers, food, sports, street, landscape and artificial. The artificial photographs were created by the authors, and the details can be found in prevous papers [15], [16]. The depth of field was fully controlled in our own photographs, and there were three levles: 5.7mm, 18.4mm, and 68.9mm respectively.…”
Section: ) Stimulimentioning
confidence: 99%
“…For this reason, many researches involving sickness in HMDs have been done recently in order to minimize sickness in these devices [8], [18], [1]. In this research, we map the various causes and symptoms of sickness that occurred during the use of HMDs (be it machine or human actions) [17], [21], [13], [3].…”
Section: Motivationmentioning
confidence: 99%